2013
DOI: 10.1128/mcb.01742-12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dissection and Stoichiometry Determination of the Human SET1/MLL Histone Methyltransferase Complexes

Abstract: Methylation of lysine 4 on histone H3 (H3K4) at promoters is tightly linked to transcriptional regulation in human cells. At least six different COMPASS-like multisubunit (SET1/MLL) complexes that contain methyltransferase activity for H3K4 have been described, but a comprehensive and quantitative analysis of these SET1/MLL complexes is lacking. We applied label-free quantitative mass spectrometry to determine the subunit composition and stoichiometry of the human SET1/MLL complexes. We identified both known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
246
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(269 citation statements)
references
References 63 publications
21
246
2
Order By: Relevance
“…Possibly, the discrepancy with the Wdr5 knockdown phenotype is due to the presence of Wdr5 in several other protein complexes [e.g. ATAC (Nagy and Tora, 2007;van Nuland et al, 2013)]. Embryos homozygous for an Ash2l hypomorphic allele showed a more severe phenotype than that of the Setd1a knockout, consistent with the inclusion of Ash2l in other H3K4 methyltransferase complexes.…”
Section: H3k4 Methyltransferases In Mouse Developmentmentioning
confidence: 53%
See 2 more Smart Citations
“…Possibly, the discrepancy with the Wdr5 knockdown phenotype is due to the presence of Wdr5 in several other protein complexes [e.g. ATAC (Nagy and Tora, 2007;van Nuland et al, 2013)]. Embryos homozygous for an Ash2l hypomorphic allele showed a more severe phenotype than that of the Setd1a knockout, consistent with the inclusion of Ash2l in other H3K4 methyltransferase complexes.…”
Section: H3k4 Methyltransferases In Mouse Developmentmentioning
confidence: 53%
“…S2). Whether the two proteins are expressed in different patterns, or at very different levels as has been recently suggested (van Nuland et al, 2013), remains to be determined. At least in ESCs, overexpression of Setd1b cannot rescue the proliferation defect caused by loss of Setd1a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MLL1, JPO2 and PogZ, we found the motif in the known LEDGF/p75 interaction partners MLL2 (ref. 41) and ASK (DBF4) from the CDC7-ASK complex 32 . Moreover, IBM and IBM-like motifs were found in the mediator complex subunit 1 (Med1; residues 891-898) and IWS1 (residues 484-491; Fig.…”
Section: Jpo2 Interacts With the Ibd Through A Disordered Regionmentioning
confidence: 99%
“…This observation suggests that the effects of DPY30 knockdown are the results of impaired H3K4me3 activity of COMPASS complexes rather than their impaired recruitment onto the chromatin, in agreement with what was reported in previous studies (Jiang et al 2011;Ernst and Vakoc 2012;Yang et al 2014). Finally, it was recently reported that DPY30 can also be found in the NURF nucleosome remodeling complex (van Nuland et al 2013), and thus we decided to investigate the binding profile of the NURF catalytic subunit BPTF on Activin/Nodal target genes. In contrast to the COM-PASS complexes, BPTF enrichment on S/N/D-bound regions was limited and independent from the presence of Activin/Nodal signaling (Fig.…”
Section: Smad2/3 Cooperates With Nanog To Recruit H3k4 Methyltransfermentioning
confidence: 99%